Phaseolin Attenuates Lipopolysaccharide-Induced Inflammation in RAW 264.7 Cells and Zebrafish - Hwang, Su-Jung (Biomedicines, 2021)
Kushen (Radix Sophorae flavescentis) is used to treat ulcerative colitis, tumors, and pruritus. Recently, phaseolin, formononetin, matrine, luteolin, and quercetin, through a network pharmacology approach, were tentatively identified as five bioactive constituents responsible for the anti-inflammatory effects of S. flavescentis. However, the role of phaseolin (one of the primary components of S. flavescentis) in the direct regulation of inflammation and inflammatory processes is not well known. In this study, the beneficial role of phaseolin against inflammation was explored in lipopolysaccharide (LPS)-induced inflammation models of RAW 264.7 macrophages and zebrafish larvae. Phaseolin inhibited LPS-mediated production of nitric oxide (NO) and the expression of inducible nitric oxide synthase (iNOS), without affecting cell viability. In addition, phaseolin suppressed pro-inflammatory mediators such as cyclooxygenase 2 (COX-2), interleukin-1β (IL-1β), tumor necrosis factor α (TNF-α), monocyte chemoattractant protein-1 (MCP-1), and interleukin-6 (IL-6) in a dose-dependent manner. Furthermore, phaseolin reduced matrix metalloproteinase (MMP) activity as well as macrophage adhesion in vitro and the recruitment of leukocytes in vivo by downregulating Ninjurin 1 (Ninj1), an adhesion molecule. Finally, phaseolin inhibited the nuclear translocation of nuclear factor-kappa B (NF-κB). In view of the above, our results suggest that phaseolin could be a potential therapeutic candidate for the management of inflammation.